Percepção ambiental na visão dos educandos do 4º e 5º ano da Escola Municipal de Ensino Fundamental Liberdade, Ananindeua/PA - SILVA, Marcia Lemos da (2019)
This paper will talk about environmental awareness of students in Municipal Elementary School in Ananindeua-PA. The environmental perception study is essential to understanding of their interrelations with the environment. To make the diagnosis was made a questionnaire on issues related to the environment, its constituent resources and human relationship with them. The questionnaire was administered to 160 students of 4° year (75 students) and 5° year (85 students), was later made tabulating data, count on frequency of respondents and were made charts to outline the results. Based on the presented results it can be seen that the students understand the environmental problems and most realize the means naturalistic environment, without human presence is necessary to make educational interventions to modify this view, and insert rearing practices environment in schools.